2009
DOI: 10.1111/j.1751-7915.2009.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of recombinant genes in Escherichia coli can be strongly stimulated at the transcript production level by mutating the DNA‐region corresponding to the 5′‐untranslated part of mRNA

Abstract: SummarySecondary structures and the short Shine–Dalgarno sequence in the 5′‐untranslated region of bacterial mRNAs (UTR) are known to affect gene expression at the level of translation. Here we report the use of random combinatorial DNA sequence libraries to study UTR function, applying the strong, σ32/σ38‐dependent, and positively regulated Pm promoter as a model. All mutations in the libraries are located at least 8 bp downstream of the transcriptional start site. The libraries were screened using the ampici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 46 publications
1
73
0
Order By: Relevance
“…Finally, one of the pJBn expression vectors has been shown to give rise to production of industrial levels of several recombinant proteins in Escherichia coli (36,37). Recently, we have found that the bla gene (encoding ␤-lactamase) expression from the Pm promoter can be strongly stimulated in E. coli (up to 20-fold at the protein product level) by introducing mutations at the DNA level in its cognate 5Ј untranslated region (UTR) (5). The inducible promoter phenotype was intact in all of the UTR variants.…”
mentioning
confidence: 99%
“…Finally, one of the pJBn expression vectors has been shown to give rise to production of industrial levels of several recombinant proteins in Escherichia coli (36,37). Recently, we have found that the bla gene (encoding ␤-lactamase) expression from the Pm promoter can be strongly stimulated in E. coli (up to 20-fold at the protein product level) by introducing mutations at the DNA level in its cognate 5Ј untranslated region (UTR) (5). The inducible promoter phenotype was intact in all of the UTR variants.…”
mentioning
confidence: 99%
“…However, the fact that larger amounts of the optimized parA mRNA were observed both in the one-copy and 14-copy parA systems (Fig. 5) may indicate that the new 5′-UTR mRNA structure is probably (Hsu et al 2006;Berg et al 2009;Goldman et al 2009) (i) increasing the stability of the complex RNA polymerase-transcript and thus reducing the amounts of abortive transcripts, (ii) decreasing the susceptibility to degradation of the transcript, and (iii) decreasing the availability to degradation because the transcript binds longer to rRNA. Thus, the final amount of the resolvase in the system is a compromise between transcriptional and translational rates.…”
Section: Discussionmentioning
confidence: 96%
“…Growth media were supplemented with 200 μg/mL ampicillin (Sigma-Aldrich) if required. Standard DNA manipulations were performed as described elsewhere (Berg et al 2009). …”
Section: Methods and Experimentsmentioning
confidence: 99%